2018
DOI: 10.1111/boer.12161
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and Optimism in a Social Dilemma

Abstract: We examine the influence of optimism about local and foreign people on social cooperation using a public goods game. Firstly, we find that optimism fuels social cooperation, and secondly, that this positive effect holds when optimism is focused either jointly or individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A possibility here is that younger individuals are less optimistic about their future and about the behaviour of others, which in turn pushes them to be instinctively more cautious about the potential consequences of their cooperative behaviour. The fact that older participants were more optimistic than younger ones also aligns with previous findings and with the socioemotional selectivity theory which posits that aging is associated with increasing motivation to derive emotional meaning from life, leading to a general positivity bias 52,53 . The fact that older people were found to be more optimistic, promoting their contributions in the PGG as well as their expectation about others' positive intentions, appears to support the claim that motivations and investments change during aging (with optimism being a mechanism driving such changes).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A possibility here is that younger individuals are less optimistic about their future and about the behaviour of others, which in turn pushes them to be instinctively more cautious about the potential consequences of their cooperative behaviour. The fact that older participants were more optimistic than younger ones also aligns with previous findings and with the socioemotional selectivity theory which posits that aging is associated with increasing motivation to derive emotional meaning from life, leading to a general positivity bias 52,53 . The fact that older people were found to be more optimistic, promoting their contributions in the PGG as well as their expectation about others' positive intentions, appears to support the claim that motivations and investments change during aging (with optimism being a mechanism driving such changes).…”
Section: Discussionsupporting
confidence: 88%
“…We also found that optimism shapes expectations about partners' contributions, so that more optimistic individuals acted more cooperatively in the PGG themselves and also expected their partners to be more www.nature.com/scientificreports/ cooperative 52 . Importantly, our data show that optimism grows with age, which can partly account for the reflective approach to cooperation in adolescence.…”
Section: Discussionmentioning
confidence: 60%
“…We also found that optimism shapes expectations about partners' contributions, so that more optimistic individuals acted more cooperatively in the PGG themselves and also expected their partners to be more cooperative 36 . Importantly, our data show that optimism grows with age, which can partly account for the reflective approach to cooperation in adolescence.…”
Section: Discussionmentioning
confidence: 56%
“…The fact that older participants were more optimistic than younger ones also aligns with previous findings and with the socioemotional selectivity theory. The latter posits that aging is associated with increasing motivation to derive emotional meaning from life, leading to a general positivity bias 36,37 . The fact that older people were found to be more optimistic, promoting their contributions in the PGG as well as their expectation about others' positive intentions, appears to support the claim that motivations and investments change during aging (with optimism being a mechanism driving such changes).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the anterior insula and IFG have been linked to the way people update beliefs relevant to personally relevant optimism biases in the face of new information (Kuzmanovic et al, 2016 ; Moutsiana et al, 2015 ). Within this optimism‐pessimism dimension a bias towards characters perceived as warm—warmth itself is linked to trust (Oyediran et al, 2018 ; Shkurko, 2013 )—played an important role.…”
Section: Introductionmentioning
confidence: 99%